UK parliamentary debate analysis: bombing ISIL in Syria. Issue 2 (2nd April 2016) - Rashed, Haifa
Abstract: This paper examines the arguments presented for and against the UK government's motion for the UK to intervene militarily in Syria in the House of Commons debate on ISIL in Syria that took place on 2 December 2015. It considers what the most common arguments were in favour of and in opposition to the motion as well as which arguments were given the most emphasis, in order to understand the prime justifications given that led to the decision to approve the motion. It suggests that due to the shadow of the 2003 Iraq war, politicians in the debate placed a considerable emphasis on the legal justification for military intervention. It argues that the focus on the national security of the UK and its allies in this particular debate seems to contrast with previous military interventions where humanitarian motives were more widely stated. This paper calls for further comparative research of parliamentary debates in order to track such changes in the rhetoric used by UK politicians to defend their support for military intervention.